Menyelaraskan Pariwisata Olahraga dengan SDGs: Tata Kelola Pacuan Kuda Tradisional di Aceh Tengah - Yoki Afriandy Rangkuti; M. Fadli Dongoran; Novriansyah Novriansyah; Arti Kurniaty Bangun; Brema Bangun (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. This study aims to evaluate the socio-economic impacts of a cultural-based sport tourism event, specifically the traditional horse racing festival in Central Aceh, and to identify governance issues affecting the sustainability of its impacts. The primary focus of the research lies in sport tourism development and sustainable growth, while physical education and learning are positioned as conceptual implications of the findings, particularly in strengthening sustainability literacy and local cultural awareness. Materials and methods. A mixed-method design with data triangulation was employed, combining quantitative surveys of local residents and business actors with qualitative data collected through in-depth interviews and Focus Group Discussions (FGDs) to capture both statistical patterns and contextual community experiences. Quantitative data were analyzed using descriptive statistics and cross-tabulation, while qualitative data were examined through thematic narrative coding. The research instruments were developed based on Social Exchange Theory and the Input–Output model, and were tested for content validity using Aiken’s V and reliability using Cronbach’s alpha. Results. The findings indicate significant short-term economic benefits: 68% of business actors reported increased income, and 57% of respondents noted the creation of temporary employment during the event. However, local inflationary pressure was observed, with essential commodity prices rising by approximately 10–15% during peak periods. From a socio-cultural perspective, 72% of respondents reported increased community pride, and more than 40% of residents participated in organizational activities or performances during the event. Infrastructure improvements were acknowledged by 61% of respondents, although concerns regarding long-term sustainability remain. In terms of governance, only 38% of respondents felt that community voices were adequately represented in the planning process. Conclusions. It can be concluded that the traditional horse racing event holds strong potential as a socio-economic catalyst in cultural-based sport tourism development. Nevertheless, strengthening inclusive governance, implementing post-event strategies, and ensuring equitable benefit distribution are essential to prevent impacts from being limited to the event period alone, while also providing meaningful implications for sustainability-oriented physical education and sport learning.